Soline on the island of Korčula – research in 2024 (In situ, 2025)
As part of the Croatian Science Foundation project (Undersea Neolithic sites in the Croatian Adriatic IP-2022-10-3893), underwater archaeological research was conducted at the Soline site in May 2024. The end of the inner side of the coastal wall was defined by exploring an area of ​​3 x 6 meters. The investigated area is higher than other parts of the coastal wall, and the structure found most likely belongs to the fortifications that are part of the entrance to the late Neolithic settlement.
Keywords: Soline; Korčula; Neolithic; settlement; HRZZ